Towards Safer Workplace: A Survey-Based Study on Developing a Safety Climate Model for the Indonesian Paper Industry - Nana Rahdiana; Bambang Suhardi; Retno Wulan Damayanti; Novie Susanto; Jafri Mohd Rohani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2024)
A reliable safety climate model is essential for evaluating safety behavior and predicting risks such as accidents or injuries, yet no research has speciﬁcally addressed the safety climate in the paper industry, either globally or in Indonesia. Recognized as high-risk due to its reliance on large machinery and hazardous chemicals, the paper industry has been understudied in this context. This research addresses the gap by developing a safety climate model tailored to the Indonesian paper industry, following a rigorous methodology that included a literature review, model design, validation processes, and Goodness-of-Fit testing. The study identiﬁed nine dimensions and 36 initial indicators, with strong content validity conﬁrmed through Aiken’s V index, and reﬁned through a survey of 313 employees—including managers, supervisors, and operators—at a paper factory in West Java, Indonesia. Conﬁrmatory factor analysis (CFA) led to the ﬁnal model, comprising nine dimensions and 32 validated indicators, achieving excellent ﬁt across key criteria. These dimensions include management commitment, safety environment, safety communication, safety involvement, safety rules and procedures, safety training, safety competence, work pressure, and local wisdom. The validated model oﬀers valuable insights into safety practices, providing a practical framework for improving safety performance in the Indonesian paper industry. By fostering a proactive safety culture and addressing sector-speciﬁc risks, this model has the potential to signiﬁcantly reduce workplace accidents and improve overall safety performance, marking an important advancement in industry-speciﬁc safety research.